Performance‐based rewards and innovative behaviors - Sanders, Karin; Jorgensen, Frances; Shipton, Helen; Van Rossenberg, Yvonne; Cunha, Rita; Li, Xiaobei; Rodrigues, Ricardo; Wong, Sut I.; Dysvik, Anders (Human Resource Management, 2018)
This study investigates the effects of two internal factors, performance‐based rewards and employee perceptions of human resource (HR) strength, and one external factor, country‐level uncertainty avoidance, on employee innovative behaviors. Drawing on situational strength theory, we first hypothesize performance‐based rewards will positively relate to innovative behaviors, and second, this relationship is stronger when employees understand the wider Human Resource Management (HRM) system as intended by management, referred to as HR strength. Finally, we assess the effect of uncertainty avoidance on the relationship between performance‐based rewards and innovative behaviors. Three‐level data from 1,598 employees and 186 managers in 29 organizations across 10 countries showed both employee perceptions of HR strength and uncertainty avoidance of a country that differentially influence the relationship between performance‐based rewards and innovative behaviors. However, a significant relationship between performance‐based rewards and innovative behaviors was not found. This study offers novel insights into how organizations can use internal factors in a systematic manner to promote innovative behaviors in their workplace, and highlights the limitations of sustaining innovative behaviors in countries characterized by high levels of uncertainty avoidance.